Sino-Yugoslav Relations in the 1949-1977 Period – The Significance of Josip Broz Tito’s 1977 Visit to the People’s Republic of China - Арежина, Сања (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Although Yugoslavia recognized the PR China immediately after its founding in 1949, Sino-Yugoslavian diplomatic relations were only established in 1955, due to bad relations between Yugoslavia and the Soviet Union. In the period 1955-1977, relations between the two countries were marked by numerous ups and downs, primarily due to the relations between the two major powers (the USA and the Soviet Union), their influence on Yugoslavia and China, as well as many other key international events. However, for the results of this research, the most important period is the period after the death of Mao Zedong and the arrest of the socalled Gang of Four in 1976, when the two countries thrived thanks to the drastic changes in their foreign policy appearances and assertive approaches and influences that projected in their region and in the globalized world to make a significant contribution to shaping the global structure. During the research, the author identified which factors positively influenced the strengthening of cooperation between the PR China and Yugoslavia. First, there is a convergence of the attitude about the fight against hegemonism and other global problems, as well as an effort to ensure that differences between them do not interfere with the cooperation. The establishment of the Sino-US relations was also very significant for the restoration of diplomatic and party relations with Yugoslavia. Particularly significant was China’s “opening up” policy to the world and the fact that Yugoslavia was not the only example of an alternative model of socialism for the Chinese, but also a significant mediator in China’s exit from self-isolation, its opening up to the third world (Non-Aligned Movement), and developing relations with Eastern European countries and the so-called Eurocommunist parties in Italy, Spain, and France, they gave Yugoslavia and China a sound foundation first. Nevertheless, the author believes that a crucial factor in strengthening the relationship between the two countries was the visionary policies of two leaders, Josip Broz Tito and Deng Xiaoping, who marked the decades-long political and economic development of both states and paved the way for next generations of leaders. That is why Josip Broz Tito’s visit to China in 1977 represents a major step forward in the relations between Yugoslavia and China, bearing in mind that it was the first visit of the President of Yugoslavia to China, during which diplomatic and party relations were restored, which contributed to strengthening the cooperation between the two countries at all levels. To prove the basic hypothesis that only after the death of Mao Zedong and the arrest of the so-called Gang of Four (in 1976) gained the conditions to strengthen the Sino-Yugoslav relations, because it outweighed the influence of positive factors versus negative factors, during the research the author will use structural-functional analysis, induction, and deduction.